Digital Pedagogy: An Essay. - Snoonian, Deborah; Cuff, Dana (Architectural Record, 2001)
Comments on the effect of digital design tools on architectural education and practice in the United States. Comparison between using digital tools and manual drawings; Influence of computing on architectural schools; Advantages of using computers in creating charrettes.